PRAGMATIC AND PERSUASIVE FUNCTIONS OF MEDIA DISCOURSE IN UZBEK AND ENGLISH NEWSPAPERS AND MAGAZINES - Fayyoza Kamolova Mirza qizi (Bright Mind Publishing, 2026)
This article investigates the pragmatic and persuasive functions of media discourse in Uzbek and English newspapers and magazines from a comparative perspective. Drawing on discourse analysis and pragmatic theory, the study examines how linguistic strategies such as evaluative language, presupposition, modality, and rhetorical devices are employed to influence readers and shape public opinion. The analysis reveals both universal and culture-specific persuasive mechanisms rooted in socio-cultural and ideological contexts. The findings contribute to media discourse studies by highlighting cross-linguistic similarities and differences in persuasive communication.
Keywords: media discourse, pragmatics, persuasion, mass media, newspaper discourse, magazine discourse, evaluative language, discourse strategies, Uzbek and English, comparative analysis